Missing heritability and strategies for finding the underlying causes of complex disease. - Eichler, E; Flint, J; Gibson, G; Kong, A; Leal, S; Moore, J; Nadeau, J (2010)
Although recent genome-wide studies have provided valuable insights into the genetic basis of human disease, they have explained relatively little of the heritability of most complex traits, and the variants identified through these studies have small effect sizes. This has led to the important and hotly debated issue of where the 'missing heritability' of complex diseases might be found. Here, seven leading geneticists offer their opinion about where this heritability is likely to lie, what this could tell us about the underlying genetic architecture of common diseases and how this could inform research strategies for uncovering genetic risk factors.